If We Are Too Small to See or You Have Forgotten: A postcolonial response to modern representations of the San in Alexander McCall Smith’s No. 1 Ladies’ Detective Agency series - Thomas, Roie (Public Journal of Semiotics, 2012)
Alexander McCall Smith’s enormously popular fiction series set in Botswana (2000-11) appears on superficial analysis to represent the San people benignly, even affectionately. Neil Graves (2010) submits that The No.1 Ladies’ Detective Agency achieves an image of “untainted and uncorrupted” Botswana through a “three-stage process of engagement, disarmament and dismissal, leaving behind a saccharine utopian Western fantasy of primitive primordial Africa” (15). However, deconstruction via a postcolonial lens shows the depictions in this text to be insidiously harmful in the light of the San’s social and political disenfranchisement in Botswana since independence. Six tropes from David Spurr’s seminal work The Rhetoric of Empire (1993) are deployed to position the various representations of the San children in this series firmly within a postcolonial critique, since such classifications clearly define the particular nuances and levels of the characters’ literary depictions.